Leishmania Exosomes/Extracellular Vesicles Containing GP63 Are Essential for Enhance Cutaneous Leishmaniasis Development Upon Co-Inoculation of Leishmania amazonensis and Its Exosomes - da Silva Lira Filho, Alonso; Fajardo, Emanuella Francisco; Chang, Kwang Poo; Clément, Pauline; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2022)
Protozoan parasites of the genus Leishmania, transmitted by the bite of infected sand flies, cause a wide range of diseases known as leishmaniasis. Recently, we demonstrated that Leishmania spp.-derived exosomes (LeishEXO) are released in the lumen of the sand fly midgut and co-egested with the parasite during the blood meal, and that LeishEXO stimulate an inflammatory response leading to exacerbated cutaneous leishmaniasis. Furthermore, it was shown that these vesicles transport important virulence factors, including GP63. Our study aimed to validate transgenic GP63-altered Leishmania amazonensis strains as a novel model to specifically address the role of GP63 in immune modulation, using morphological & proteomic analyses. We then set out to study the impact of different GP63 vesicle expression levels on their ability to modulate innate inflammatory cell responses, and finally to determine the importance of GP63 vesicle content on the exacerbation of cutaneous Leishmania spp. pathology after host co-inoculation. Our results revealed that GP63 was the sole virulence factor altered among the composition of extracted exosomes/extracellular vesicles (EVs), confirming the specificity of the model in question. We further demonstrated that vesicles with different GP63 exosome/EV cargo displayed distinctive macrophage immunomodulatory capabilities at both the gene and protein expression levels in vitro. Finally, we determined these vesicles’ impact on Leishmania spp. cutaneous pathology in an in vivo setting and confirmed GP63 as a primordial component of these exosomes/EVs ability to increase inflammatory response in an infection setting. Our findings provide new insight into the cutaneous leishmaniasis immune response and shed light on the mechanism behind the host-pathogen interaction occurring in the initial moments of infection, identifying enriched GP63 in Leishmania spp.-derived exosomes/EVs as an important player. This opens the door to promising new targets for Leishmania pharmacological treatments and vaccinations.